Ambiguous Figures – What Happens in the Brain When Perception Changes But Not the Stimulus - Kornmeier, Jürgen; Bach, Michael (Frontiers in Human Neuroscience, 2012)
During observation of ambiguous figures our perception alternates spontaneously although the visual information stays unchanged. Research on this phenomenon so far suffered from the difficulty to determine the instant of the endogenous reversals with sufficient precision. A novel experimental paradigm with discontinuous stimulus presentation improved on previous temporal estimates of the reversal event by factor 3. It revealed that disambiguation of ambiguous visual information takes roughly 50 ms or two loops of recurrent neural activity. Further, the decision about the perceptual outcome has taken place at least 340 ms before the observer is able to indicate the consciously perceived reversal manually. We provide a short review about physiological studies on multistable perception with a focus on electrophysiological data and present a new perspective on multistable perception that can easily integrate previous apparently contradicting explanatory approaches. Finally we propose possible extensions towards other research fields where ambiguous figure perception may be useful as an investigative tool.